The handwriting expert and its probative value in Malaysia / Ramalinggam Rajamanickam, Anita Abdul Rahim and Anisah Che Ngah - Rajamanickam, Ramalinggam; Abdul Rahim, Anita; Che Ngah, Anisah (Faculty of Administrative Science and Policy Studies, 2012)
In the area of globalization, infringement of rights either through civil or criminal activities is increasing and people come to the court to settle their disputes as well as to obtain justice. The court solves the disputes mainly through the testimony of witnesses. Generally, a witness is not allowed to give an opinion in the court of law. However, this principle subject to an exception whereby the court may permits the expert witnesses to state their opinion pertaining to any issue in disputes. One of the important areas which the expert may give his or her opinion is the field of handwriting. Thus, this writing focuses on the relevancy of the handwriting expert under the Evidence Act 1950. This writing also explains the admissibility of such evidence and its probative value in a case.